UDL as an Educational Framework to Improve Attitude and Reading Comprehension in Primary Education - Larragueta Arribas, Marta; Benítez Jaén, Ana María; Moraleda Ruano, Álvaro (Journal of Learning Styles, 2025)
This study examines the impact of Universal Design for Learning (UDL) on reading comprehension in Primary Education through an intervention designed by xxxxxxxxxxxxxxx. A sample of 67 students from three schools participated in the study, implementing inclusive strategies based on UDL principles, with a special focus on engagement and representation. The research follows a quasi-experimental design with pretest-posttest measurement without a control group. The EDICOLE (Diagnostic Evaluation of Reading Competence) tool was used to assess students' reading comprehension and their attitude towards reading. The results indicate that no statistically significant differences were found in reading comprehension ability after the intervention. However, an improvement in students' attitudes towards reading was observed. Specifically, there was an increase in interest and a decrease in perceived difficulty, particularly among female students. These findings suggest that UDL enhances motivation and learning perception, reinforcing the importance of designing flexible and inclusive educational environments. However, certain methodological limitations, such as the lack of a control group, should be addressed in future research.
Keywords: Universal Design for Learning; reading comprehension; Primary Education; inclusive education; attitudes towards reading